2019
DOI: 10.3390/molecules24030414
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Roseoside and Icariside E4 Isolated from a Natural Product Mixture (No-ap) on the Expression of Angiotensin II Receptor 1 and Oxidative Stress in Angiotensin II-Stimulated H9C2 Cells

Abstract: Hypertension is a major risk factor for the development of cardiovascular diseases. This study aimed to elucidate whether the natural product mixture No-ap (NA) containing Pine densiflora, Annona muricate, and Monordica charantia, or its single components have inhibitory effects on hypertension-related molecules in Angiotensin II (Ang II)-stimulated H9C2 cells. Individual functional components were isolated and purified from NA using various columns and solvents, and then their structures were analyzed using E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
(58 reference statements)
2
11
0
Order By: Relevance
“…Extracellular signal-related kinases (ERK1/2), c-Jun N-terminal kinases (JNK1/2), and p38 kinase (p38) are three MAPKs that have been reported to be involved in cardiac hypertrophy [ 3 ]. Activation of AT1R by Ang II also activates NADPH oxidase that increases the generation of reactive oxygen species (ROS), particularly superoxide anion [ 4 ]. Superoxide dismutase (SOD) converts the anion to less reactive molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular signal-related kinases (ERK1/2), c-Jun N-terminal kinases (JNK1/2), and p38 kinase (p38) are three MAPKs that have been reported to be involved in cardiac hypertrophy [ 3 ]. Activation of AT1R by Ang II also activates NADPH oxidase that increases the generation of reactive oxygen species (ROS), particularly superoxide anion [ 4 ]. Superoxide dismutase (SOD) converts the anion to less reactive molecules.…”
Section: Introductionmentioning
confidence: 99%
“…According to our LC-MS analyses, PTP contained large amounts of quinic acid, which has been reported to possess potent antioxidant properties and antineuroinflammatory activity [ 33 ]. Furthermore, PTP contains roseoside and icariside E4, which are known to alleviate oxidative stress [ 34 ], as well as pinocembrin, which also possesses anti-inflammatory effects [ 35 ]. Therefore, our study is the first to identify PTP as a novel potential natural anti-inflammatory agent.…”
Section: Discussionmentioning
confidence: 99%
“…ICA II could alleviate LPS-induced neuroinflammation by inhibiting the TLR4 / MyD88 /NF-κB pathway, and also alleviate eosinophilic airway inflammation and remodeling by inhibiting the NF-κB and STAT3 pathways in an asthma mouse model [11]. Notably, many studies showed the effects of ICA II on inflammatory response and oxidative stress [19]. ICA II overcome BRAF inhibitor resistance in melanoma via the induction of ROS production [20].…”
Section: Discussionmentioning
confidence: 99%